Intelligent collaborative management and control platform for continuous mining equipment in open-pit mines - Zhiyong LEI; Xiaolong MA; Shujun ZHAO; Shiming ZHANG; Bin YAN (Meitan kexue jishu)
This research presents the development of an intelligent control platform for continuous coal mining equipment in open-pit mines, aimed at enhancing operational efficiency, reducing labor intensity, and advancing automation. The platform integrates advanced technologies, including dual-ring network transmission, network security protocols, multi-machine cooperative control, digital twin modeling, and big data analytics, facilitating effective coordination among coal miners, transfer machines, unloaders, and conveyors for seamless continuous mining operations.Three critical technical challenges are addressed: ① The implementation of dual-ring network transmission technology reduces data transmission latency and enhances network stability. ② A secure network transmission framework has been developed to safeguard data confidentiality and integrity. ③ The multi-machine cooperative control system incorporates data acquisition, process control, and 3D visualization modules, employing real-time monitoring and optimized control algorithms to boost mining and transportation efficiency while ensuring the continuity of multi-machine operations. Leveraging digital twin theory, a synchronized multi-machine digital twin system is constructed to address data integration and real-time responsiveness issues prevalent in open-pit mining. A unified communication standard is established to support diverse protocols, ensuring robust information sharing among equipment. Additionally, edge computing technology is utilized for rapid field data processing, minimizing latency and facilitating real-time analysis and decision-making. This significantly enhances monitoring and control capabilities, achieving a high degree of synchronization between the digital model and physical operations. The platform delivers multiple functionalities, including comprehensive multi-machine synchronous monitoring, online fault self-diagnosis, and early warning systems, alongside improved multi-machine cooperative control efficiency. Test results indicate that the platform successfully achieves multi-machine synchronous control, with a data packet loss rate of ≤ 0.25% and latency of ≤ 2 seconds, enabling coal extraction of 11 meters with an annual production capacity of 130000 tons, while maintaining a failure-free rate of up to 90% during continuous operation. All functionalities align with actual production requirements.